“Drying effect” of fructus aurantii components and the mechanism of action based on network pharmacology and in vitro pharmacodynamic validation - Zhu, Jing; Luo, Yi; Tong, Hengli; Zhong, Lingyun; Gong, Qianfeng; Wang, Yaqi; Yang, Ming; Song, Qing (Frontiers in Pharmacology, 2023)
Background: Fructus aurantii (FA) is the dry, immature fruit of the plant Citrus aurantium L. and its cultivated varieties. We investigated the “drying effect” of FA components and how the drying affect is achieved. Methods: We employed systems pharmacology to predict the components and targets of FA that produce its drying effect. These predictions were verified by computer simulation and animal experiments. In the latter, we measured the bodyweight, water consumption, urine output, fecal water content, rate of salivary secretion, and cross-sectional area of the long axis of the submandibular gland of mice. Immunohistochemistry was used to measure expression of aquaporin (AQP)5 in the submandibular gland, AQP2 in the kidney, and AQP3 in the colon. ELISA kits were used to measure changes in levels of cyclic adenosine monsophosphate (cAMP), cyclic guanosine monophosphate (cGMP) and interferon-γ. Results: Sixty-seven potentially active components of FA were screened out. FA could regulate 214 targets through 66 active components, and then produce a drying effect. A total of 870 gene ontology (GO) terms and 153 signaling pathways were identified. The hypoxia inducible factor-1 signaling pathway, phosphoinositide 3-kinase-protein kinase B (PI3K-AKT) signaling pathway, calcium signaling pathway, and Ras signaling pathway may have important roles in the drying effect of FA. Four components of FA were identified: sinensetin, tangeretin, 5-demethylnobiletin and chrysin. These four components could increase the serum level of interferon-γ and ratio of cyclic adenosine monophosphate:cyclic guanosine monophosphate in mice, and affect their water consumption, urine output, fecal water content and rate of salivary secretion. Conclusions: Four components of FA (tangeretin, sinensetin, chrysin, 5-Demethylmobiletin) are closely related to the Janus kinase-signal transducer and activator of transcription-3, PI3K-AKT, and other signaling pathways. These components have a role in the drying effect of FA if it is used in a TCM formulation.